KORELASI KETERAMPILAN MEMAHAMI TEKS DESKRIPSI DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 15 PADANG - Tressyalina, Deta Fitrianita, Syahrul R., (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This article was written to find out the correlation between comprehension and writing skill of description text for student at class VII SMPN 15 Padang. Data in this study was score of text comprehension skill. The type of this study was quantitative research with correlation design. Study population was students at class VII SMPN 15 Padang that enrolled in academic year of 2016/2017 with sample was amounted to 224 students that dispersed in seven classes. Sampling determination used proportional random sampling technique that obtained 42 students (20% from student population per class). Study fining showed that there was a significant correlation between comprehension and writing skill of description text for student at class VII SMPN 15 Padang with tcount > ttable (10.32 > 1.68). Therefore, to write description text students should be able to understand the description text it self. Kata kunci: korelasi, keterampilan memahami teks deskripsi,  keterampilan menulis     teks deskripsi